A Modular Algorithm for Dynamic Design of Large-Scale Experiments - Nikolaus Haselgruber (Austrian Journal of Statistics, 2016)
Large-scale experiments usually run on carriers (e.g., test benches in technical industry) which may have individual limitations concerning the setting of certain design factors. Consequently, this leads to restricted factor ranges for single realizations of the experiment. This article discusses a modular algorithm for the generation of a D-optimal design based on the point exchange principle. For single experiments, fixed and partly fixed factor settings can be considered. The term dynamic refers to the possibility of experiment-specific design adaptations.